1997
DOI: 10.1023/a:1005777219997
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen increases intracellular p26Bcl-2 to p21Bax ratios and inhibits taxol-induced apoptosis of human breast cancer MCF-7 cells

Abstract: Recent studies have demonstrated that following estrogen ablation, estrogen responsive breast cancer cells undergo apoptosis. In addition, estrogen receptor (ER) expression has been strongly correlated with the expression of the bcl-2 gene product, p26Bcl-2 protein, which is known to inhibit apoptosis. In the present studies, we investigated whether estrogen affects the intracellular levels of p26Bcl-2 and thereby modulates taxol-induced apoptosis of estrogen responsive human breast cancer MCF-7 cells. Transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 17 publications
10
97
1
Order By: Relevance
“…29,30 Phosphorylation of BCL-2 interferes with its dimerization with the proapoptotic protein BAX and can thus induce cells to undergo apoptosis. 31 Evidence was obtained in the present study that 2-MeOEMATE could induce BCL-2 phosphorylation in HUVECs as previously found to occur in MCF-7 cells. 16 Changes in HUVEC morphology and the assessment of free nucleosome levels in drug-treated cells confirmed that these cells were undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…29,30 Phosphorylation of BCL-2 interferes with its dimerization with the proapoptotic protein BAX and can thus induce cells to undergo apoptosis. 31 Evidence was obtained in the present study that 2-MeOEMATE could induce BCL-2 phosphorylation in HUVECs as previously found to occur in MCF-7 cells. 16 Changes in HUVEC morphology and the assessment of free nucleosome levels in drug-treated cells confirmed that these cells were undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with previous ®ndings (Huang et al, 1997b;Saunders et al, 1997), Taxol-induced apoptosis in MCF-7 cells. Morphological analysis of Taxoltreated cells revealed cardinal features of apoptosis including chromatin condensation and nuclear fragmentation (Figure 1).…”
Section: Taxol-induced Apoptosis Is Associated With Activation Of Erksupporting
confidence: 93%
“…We first analysed cells grown in normal conditions (phenol red containing medium and complete FCS) and cells additionally exposed for 2 or 4 days to the pure anti-oestrogen ICI 182 780 (Wakeling et al, 1991). Consistent with previous reports (Texeira et al, 1995;Huang et al, 1997), exposure of MCF7 cells to ICI 182 780 significantly down-regulated BCL-2 expression ( Figure 5). By contrast, BAG-1 expression was not altered.…”
Section: Effects Of Oestrogen On Bag-1 and Bcl-2 Expression In Mcf7 Csupporting
confidence: 92%
“…Indeed, BCL-2 is regulated by oestrogens in breast cancer cells (Texeira et al, 1995;Huang et al, 1997) and BAG-1 and BCL-2 are co-regulated in some systems (Adachi et al, 1996). We therefore examined effects of modulating oestrogen signalling on BAG-1 and BCL-2 expression in oestrogen-responsive MCF7 cells.…”
Section: Effects Of Oestrogen On Bag-1 and Bcl-2 Expression In Mcf7 Cmentioning
confidence: 99%
See 1 more Smart Citation